1193 How to Use C-Reactive Protein in Septic Screening of Term and Near Term Newborns?. (October 2012) - Rebelo, D; Santos, T; Albuquerque, M; Oliveira, G; Rodrigues, T
Abstract : Background and Aims: Early onset sepsis is a serious condition, with challenging diagnosis. C-Reactive Protein cut-off values for treatment vary according to different authors and protocols from 5 mg/L to 50 mg/L. The objective of this study was to determine the CRP cut-off value in septic screening of term and near term NB. Methods: All NB with gestational age (GA) ³ 35 weeks admitted to the nursery of a tertiary hospital in the course of one year, with risk for early neonatal sepsis where included. We collected data from all analysis (CRP/CBC) until treatment decision, peripheral blood-culture and clinical findings. A positive septic screening (indicating treatment) resulted from a score involving CRP and leukocy te/neutrophil count. Newborns were thereafter included in the category "presumption of infection" (POI) if they met at least one of the following criteria: CRP > 50 mg/L; maternal sepsis; NB with positive blood-culture; several positive markers and subtle clinical features; multiple risk factors and subtle clinical features. Results: From 2478 NB admitted, 193 were included, mean GA 38.7 weeks. CRP for untreated NB varied between 10 and 16mg/L. Those that underwent antibiotic therapy had CRP values between 10 and 151mg/L. CRP for NB with POI varied between 22 and 151mg/L, treated but with no late presumption of infection between 10 and 48mg/L. A cut-off level of 20mg/l would have selected 16 without POI and missed none. Conclusions: The authors recommend for this population to use a cut-off level of 20mg/L to start antibiotics.